The Impact of Tempe Wastewater on the Anatomical Structure and β-Carotene Content of Water Spinach (Ipomoea aquatica Forsk) - Fardiaz, Mohammad; Rasyid, Benjamin Rade (Institute for Law and Economics Studies, 2024)
This study explores the impact of tempe wastewater on the anatomical structure and β-carotene content of water spinach (Ipomoea aquatica Forsk.), aiming to evaluate the potential benefits of utilizing nutrient-rich wastewater in agricultural practices. Water spinach plants were irrigated with varying concentrations of tempe wastewater and compared to control plants irrigated with freshwater. Anatomical analysis revealed significant changes in treated plants, including increased leaf thickness, higher stomatal density, enhanced stem diameter, and more extensive root branching, indicating improved plant growth and nutrient uptake capabilities. High-Performance Liquid Chromatography (HPLC) analysis showed that the average β-carotene content in treated water spinach was 52.5 µg/g, significantly higher than the 46.1 µg/g observed in control plants. These findings suggest that tempe wastewater enhances both the anatomical structure and nutritional quality of water spinach. The study concludes that tempe wastewater can be a sustainable irrigation source, offering environmental benefits and improved crop nutrition.